Eating supper on a sinking ship: Acts 27:27–38. (August 2019) - May, David M.
The sea-journey adventure of Paul in Acts 27:27–38 serves as the focus of this sermon. The author of Luke–Acts illustrates that, during the storm crisis, prisoner Paul is the true leader of this ship, even above the captain and centurion. Paul's leadership and faith are demonstrated in the celebration of a meal with all those on board. Using key language, such as "giving thanks, " "bread, " and "breaking, " the meal scene echoes the Lord's Supper. Amid crises, participating in the Lord's Supper provides a sense of hope, community, and encouragement.